Quantitative and sensitive sequencing of somatic mutations induced by a maize transposon - Justin Scherer; Michael Hinczewski; Brad Nelms (Proceedings of the National Academy of Sciences, 2025)
Cells accumulate mutations throughout development, contributing to cancer, aging, and evolution. Quantitative data on the abundance of de novo mutations within plants or animals are limited, as new mutations are often rare within a tissue and fall below the limits of current sequencing depths and error rates. Here, we show that mutations induced by the maize Mutator (Mu) transposon can be reliably quantified down to a detection limit of 1 part in 16,000. We measured the abundance of millions of de novo Mu insertions across four tissue types. Within a tissue, the distribution of de novo Mu allele frequencies was highly reproducible between plants, showing that, despite the stochastic nature of mutation, repeated statistical patterns of mutation abundance emerge. In contrast, there were significant differences in the allele frequency distribution between tissues. At the extremes, root was dominated by a small number of highly abundant de novo insertions, while endosperm was characterized by thousands of insertions at low allele frequencies. Finally, we used the measured pollen allele frequencies to reinterpret a classic genetic experiment, showing that evidence for late Mu activity in pollen is better explained by cell division statistics. These results provide insight into the complexity of mutation accumulation in multicellular organisms and a system to interrogate the factors that shape mutation abundance.